Ki67 as a prognostic factor for long-term outcome following surgery in gastrointestinal stromal tumors. Issue 11 (November 2015) - Turkel Kucukmetin, Nurten; Cicek, Bahattin; Saruc, Murat; Ersoy, Ozdal; Vardareli, Eser; Onder, Oguz; Gurluler, Ercument; Tiftikci, Arzu; Goksel, Suha; Tozun, Nurdan
Abstract : Objective: This study aimed to examine the value of Ki67 expression along with other potential prognostic factors for predicting overall survival and disease-free survival in patients with gastrointestinal stromal tumors who underwent curative resection. Patients and methods: Sixty-eight histologically confirmed and operated patients with gastrointestinal stromal tumors were included. Clinical and follow-up data were retrieved from medical records and patients were contacted at the end of the study. The effects of certain clinical and histopathological parameters on survival outcomes were examined. Results: Sixty-eight patients were followed for a mean duration of follow-up of 2923.3 patient-months. Twelve deaths (17.6%), seven metastasis (10.3%), and two local recurrences (2.9%) occurred. Overall survival was 102.5 months [95% confidence interval (CI), 88.3–116.8] and disease-free survival was 91.8 months (95% CI, 76.5–107.2). Multivariate analyses identified a high Ki67 index (≥10%) as an independent predictor of both poor overall survival (hazard ratio, 4.8; 95% CI 1.2–19.2; P =0.027) and poor disease-free survival (hazard ratio, 15.3; 95% CI, 4.7–50.2). Conclusion: A high Ki67 expression seems to be a useful prognostic factor that would aid in predicting disease course in gastrointestinal stromal tumors. These findings deserve further investigation in larger studies.